(untitled) (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2024)
In this study, consisted of 96 customers from Eromoko Jaya Store in Tanah Abang, Central Jakarta were involved and equipped with a questionnaire using the Likert Scale, after analyzing the respondents’ answers using SPSS version 25 software, The research findings indicate that the variables of price perception and product quality have a significant influence on purchase decisions, while Promotion does not have a significant influence on purchase decisions.